DEVELOPMENT AND COMPARISON OF ORALLY INHALABLE SUSTAINED RELEASE FORMULATIONS FOR THREE RESPIRATORY DRUGS FOR ASTHMA - kumar, K.Sathish; Kumaresan, C.; Anantharaj, R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The present work was designed to develop and compare orally inhalable sustained release formulation for salbutamol sulphate (SS), ambroxol hydrochloride (AH) and montelukast sodium (MS).The emulsion solvent evaporation method was used to prepare microparticles with the polymers. The prepared polymer encapsulated microparticles were blended with carrier inhalable lactose and filled in size 3 hard empty gelatin capsule. Formulations T1-T9 were prepared with 1:1 ratio of PLGA (50:50), PLGA (75:25) and Eudragit RS100. The formulation T1 prepared with SS:PLGA (50:50) produces best result when compared with other formulations T2-T9. Formulation T1 gives in vitro release 91.23% at 12 h and having particle size of microparticles (D0.5 µm) 1.94±0.6 and respiratory fraction 34.9± 2.59 %.